Resistance Profile of Extended Spectrum Beta Lactamase-Producing Escherichia coli Bacteria using Vitek® 2 Compact Method - Freshinta Jellia Wibisono; Bambang Sumiarto; Tri Untari; Mustofa Helmi Effendi; Dian Ayu Permatasari; Adiana Mutamsari Witaningrum (Buletin Peternakan, 2020)
This study aimed to determine the resistance profile and the nature of multidrug resistance in Extended Spectrum Beta Lactamase (ESBL)-producing Escherichia coli (E.coli) against several classes of antibiotics. Positive isolates of ESBL-producing E.coli were tested for antibiotic sensitivity using the VITEK® 2 compact method which then analyzed automatically. The results showed an antibiotic resistance profile against ESBL-producing E.coli showed the highest level of antibiotics in beta lactam, amoxicillin, ampicillin, cefazolin, cefotaxime, and ceftriaxone at 100%. Subsequent results found a relatively high level of resistance in the antibiotics aztreonam (86.36%), trimethoprim/sulfamethoxazole (77.27%), gentamicin (72.73%), and ciprofloxacin (68.18%). Antibiotics from carbapenem groups such as ertapenem and memenem, and antibiotics from the aminoglycosides (amicasin) and tigecycline groups of tetracycline still showed a high sensitivity level of 100%. The most common resistance patterns found in ESBL-producing E.coli isolates are AM/AMP/KZ/CTX/CRO/ATM/GM/CIP as much as 22.73%, and AM/AMP/KZ/CTX/CRO/ATM/GM/CIP/SXT patterns of 18.2%. The results of multi-class antibiotic resistance showed that 86.36% had multidrug resistance. The highest multidrug resistance pattern in ESBL-producing E.coli occurred with a BL/AG/Q/SP pattern of 50%. Other patterns of multidrug resistance in ESBL-producing E.coli that can be found in this study are, the BL/AG/Q/SP pattern is 18.20%, the BL/AG/Q/SP pattern is 13.64%, and the BL/AG/Q pattern is 4.55%. The high profile of resistance and the nature of multidrug resistance in ESBL-producing E.coli has the potential to spread these resistant genes, thus risking the use of antibiotics as a public health therapy and animal health, therefore further evaluation and control are needed.